Mathamatical model of nitrite content in the pickled potherb mustard - YANG Xing-min; LIU Qing-mei; XI Li-feng; YANG Liu-ming (浙江大学学报. 农业与生命科学版, 2004)
The effect of some factors including fermentation method, the content of salt and the species on the content of nitrite during the process of pickling of potherb mustard was investigated by using the L4 (23) orthogonal experiment. Two mathematical models were provided. The results showed that one is a valid linear model that was estimated according to least twain-multiplication. The findings attained by this model was consistent with what were found in the process of pickling of potherb mustard. The other is a neural network model, which, combined with “ Matlab ” software and “ Levenberg-Marquardt” exercitation means, precision arrived at 10-7 through 180 exercitations. It showed that the latter was superior to the former in the process of pickling of potherb mustard.